PELAKSANAAN PROGRAM MAKAN BERGIZI GRATIS DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI SMKS INDONESIA MAS KARAWANG - Yusi Fatimah Zahra; Hinggil Permana; Taufik Mustofa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the management of the Free Nutritious Meal Program and its contribution to students’ learning motivation at SMKS Indonesia Mas Karawang. The study was motivated by the finding that some students came to school without breakfast and showed low concentration, sleepiness, and limited participation during morning lessons. A qualitative case-study approach was employed. Data were collected through observation, interviews, and documentation involving the principal, teachers, and the program coordinator, then analyzed through data reduction, data display, and conclusion drawing. The findings show that program planning was aligned with the school’s vision and supported by the optimization of available human resources and facilities. Organizing was carried out through delegation of tasks and continuous coordination between the school and the food provider. Implementation ran in an orderly manner and helped students feel more physically prepared for learning, although the increase in learning motivation had not yet appeared in a fully significant way. Supervision was conducted through direct monitoring, gradual evaluation, and anticipatory improvements, especially in menu variation and distribution timing. The study concludes that the program has been managed fairly well, but its effectiveness can be strengthened through better scheduling, more adaptive menu planning, and closer integration with classroom learning strategies.